Changes in reaction surface during the methane hydrate dissociation and its implications for hydrate production. (1st September 2021) - Zhang, Yongchao; Wan, Yizhao; Liu, Lele; Wang, Daigang; Li, Chengfeng; Liu, Changling; Wu, Nengyou
Abstract: The reaction surface area of hydrate (RSAH) inherently controls the reaction rate of hydrate dissociation in the pore spaces, which further affects the gas production behaviour of the hydrate-bearing sediments. The objective of this work is to measure and describe the RSAH evolution during MH dissociation and analyse its implications for gas production. The CT images obtained from different dissociation stages showed the RSAH decreased slowly in the early stage of dissociation and rapidly in the later stage. By considering the pore structure features of sediment, a fractal method was proposed to predict the relationship between RSAH and hydrate saturation, which showed better agreement with the CT experimental results than that of Yousif's model. Further hydrate production numerical simulations embedded with different RSAH predictions indicated that the hydrate production process was significantly influenced by the variations in RSAH. The simulated gas production rate based on the fractal model was lower than that of Yousif's model, the far-field pressure drop in the fractal model was slower, and the advance of the dissociation front and the transfer of the pressure field in Yousif's model was faster than that of the fractal model. Highlights: The changes in hydrate reaction surface area during hydrate dissociation are experimentally measured and analysed. A fractal model considering the pore structure characteristics of porous media is proposed and experimentally validated. A comparison of the hydrate dissociation rate predicted by the proposed fractal model and by Yousif's model is made. Implications of reaction surface evolution during the hydrate dissociation for hydrate productions are modeled.